Hubungan Antara Asupan Kalium Dengan Tekanan Darah Pada Lanjut Usia Di Posyandu Lansia Ngudi Waras Di Desa Blulukan, Kecamatan Colomadu, Kabupaten Karanganyar - Prakoso Imammudin, Wildan, Elida Soviana,S.Gz., M.Gizi (2016)
Backround. Blood Pressure is the pressure which is inflicted on artery wall. The highest blood pressure occurs during ventricle contracts it called the systolic blood pressure, while the lowest blood pressure occurs when the heart relaxes it called diastolic blood pressure. Normally blood pressure average around 120/80 mmHg. Objective. This research aims to know the correlation between potassium intake and elderly blood pressure. Method. Type of research is observational with cross sectional approach by measuring dependent variable and independent variable simultaneously. The number of sample requires 36 person. The potassium data taken by using FFQ semi quantitative, blood pressure measured by using sphygmomanometer stated in mmHg. Data Potassium intake with systolic and diastolic data taken by using Rank Spearman correlation test. Result. Elderly potassium intake in posyandu lansia ngudi waras 2,8% has a good result, 97,2% is less of potassium intake. Elderly blood pressure in posyandu lansia ngudi waras 25% prehypertension, 47,2% hypertension level 1, 2,8% hypertension level 2. The correlation between potassium intake and systolic blood pressure ρ value= 0,906, the correlation between potassium intake and diastolic ρ value= 0,490. Conclusion. There is no correlation between potassium intake with systolic and diastolic blood pressure . Keywords : blood pressure, potassium intake, hypertension, elderly.